2018
DOI: 10.1016/j.ihj.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Lead aVR is a predictor for mortality in heart failure with preserved ejection fraction

Abstract: BackgroundNormally, lead augmented vector right (aVR) has a negative T wave polarity (TaVR) in the electrocardiography (ECG). Positive TaVR and ST segment deviation in lead aVR (STaVR) have negative effects on mortality in heart failure with reduced ejection fraction patients.AimOur aim was to investigate the relationship between lead aVR changes and mortality in heart failure with preserved ejection fraction (HFpEF) patients.MethodsWe retrospectively examined 249 patients in 2011–2015 years (mean age 70.8 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…In another study, in patients with anterior myocardial infarction, positive T wave in lead aVR showed global left ventricular ischemia. Recent studies have shown that the T-wave positivity in the lead aVR is a marker of ventricular repolarization abnormality and provides information on short- and long-term cardiovascular mortality in patients with heart failure, patients with anterior myocardial infarction, and those who receive hemodialysis for various reasons 15 17 . In their long-term follow-up study of male individuals, Tan et al showed that the T-wave positivity is an independent risk factor for cardiovascular events 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, in patients with anterior myocardial infarction, positive T wave in lead aVR showed global left ventricular ischemia. Recent studies have shown that the T-wave positivity in the lead aVR is a marker of ventricular repolarization abnormality and provides information on short- and long-term cardiovascular mortality in patients with heart failure, patients with anterior myocardial infarction, and those who receive hemodialysis for various reasons 15 17 . In their long-term follow-up study of male individuals, Tan et al showed that the T-wave positivity is an independent risk factor for cardiovascular events 20 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it provides prognostic information on many cardiovascular diseases. A positive T-wave amplitude in the lead aVR gives prognostic information on repolarization abnormality and provides diagnostic and prognostic information on many cardiovascular diseases such as in heart failure 15 17 . However, there is no information regarding its relationship with COVID-19 pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lead aVR ST elevation could represent a "mirror image" of ST depression in the lateral leads, which reflects diffuse LV subendocardial ischemia (19,20). aVRT+ has been associated with unfavorable outcome in patients with an implantable cardioverterdefibrillator, heart failure with preserved LV ejection fraction, transcatheter aortic valve implantation, ischemic cardiomyopathy, and hemodialysis therapy (6,7,21,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The T wave in lead aVR is normally negative due to the unique location of this augmented extremity lead. However, previous studies have shown that a positive or isoelectric T wave (aVRT+) in a routine 12-lead ECG is an independent prognostic predictor of cardiovascular mortality in the general population as well as in cardiovascular disease (1)(2)(3)(4)(5)(6)(7)(8). Changes in lead aVR are also important in the differential diagnosis of tachyarrhythmias (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, it provides prognostic information on many cardiovascular diseases. A positive T-wave amplitude in the lead aVR gives prognostic information on repolarization abnormality and provides diagnostic and prognostic information on many cardiovascular diseases such as in heart failure [15][16][17] . However, there is no information regarding its relationship with COVID-19 pneumonia.…”
mentioning
confidence: 99%